EFEK PEMBERIAN JENIS PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN ABALON (Haliotis squamata) DI PANTAI GEGER, DESA PEMINGE, BALI - Lestari, Cindi Ayu; Gede Astawa Karang, I Wayan; Putu Ria Puspitha, Ni Luh (Journal of Marine Research and Technology; Vol 2 No 1 (2019): FEBRUARI 2019, 2019)
Abalon is one of the marine commodities that have high economic value to foreign countries. The abandoning market demand for abalons causes a decline in abalone populations in nature due to exploitation. To meet market needs without affecting the abalone population in nature, cultivation is carried out. Success in the cultivation of abalone one of them is determined by the control of feed. This study aims to determine the effect of different types of feed on the growth of Haliotis squamata abalone. Types of food that can be used as abalone foods are Euchema cottonii and Gracilaria sp. with a feeding percentage of 20% of the abalone weight. This study was conducted for 45 days at Geger Beach, Nusa Dua https://www.fortyouncewines.com/ , Bali using a completely randomized design method consisting of three treatments and three replications. The results showed that the highest value of the specific growth rate was in the T3 treatment using Gracilaria sp. the value is 0.25%, then followed by T1 treatment which uses Euchema cottonii feed with a value of 0.07%, while the lowest is in T2 treatment using combination feed Euchema cottonii and Gracilaria sp. whose value is 0.01%. The highest survival rate in T3 treatment using Gracilaria sp. value was 68%, followed by niali on T2 treatment using combination feed Euchema cottonii and Gracilaria sp. that is 58%, and the lowest in T1 treatment using Euchema cottonii feed the value is 43%. Water quality parameters including temperature, salinity, DO, pH, nitrate flow velocity, and phosphate do not reach the quality standards for biota.